Trends of Blood and Plasma Donations in Kazakhstan: 12-Years Retrospective Analysis. - Nurbek Igissinov; Dariyana Kulmirzayeva; Raushan Magzumova; Cees Th Smit Sibinga; Sholpan Alpeissova (Tehran University of Medical Sciences, 2014)
Each country faces a continuing challenge to collect enough blood to meet the national needs. According to WHO, there should be at least 20 blood donations per 1,000 population for developing countries, in Kazakhstan this indicator was only 16.8 in 2011. Thus, we conducted an epidemiological assessment and drew a map of the regional distribution of blood and plasma donations in Kazakhstan during the years 2000-2011.The retrospective study was conducted from 2000 to 2011. Data on blood and its components donations were acquired from the Ministry of Health (annual statistical reporting form N° 39).During 2000-2011, number of blood donors decreased to 17.4% and blood donations to 6.3%. The proportion of non-remunerated blood donations and donors decreased from 97.6% to 77.9% and 97.9% to 87.7%, respectively. The paid donations had the opposite trend. Number of plasma donors increased in 2.1 times, plasma donations in 2.4 times, nevertheless the proportion of non-remunerated plasma donations decreased from 60.1% to 29.8%. The average number of blood donations per 1,000 population decreased from 19.8 (2000) to 16.8 (2011), plasma donations increased from 1.4 to 3.1. Regionally, annual average rates of blood and plasma donations per 1,000 population over 12 years varied greatly.This is the first study conducted in Kazakhstan to provide detailed information, including the regional characteristics of blood and plasma donations over an extended period of time, which can be used in blood transfusion services work.